2021
DOI: 10.29313/mimbar.v37i1.7011
|View full text |Cite
|
Sign up to set email alerts
|

Design of Bag Product’s Marketing Strategy by Implementing QFD Method and SWOT Analysis

Abstract: Production of children's backpacks has experienced a decline in sales over the past three years. This is experienced by CV Semesta Agung (SA), a textile company that produces t-shirts, jeans, and children's backpacks. The decline of children's backpacks sales occurred because of the large number of competitors and it needs a solution to overcome it. This research aims to design the marketing strategy by implementing QFD method and SWOT analysis. The method used is Quality Function Deployment (QFD) stage one, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…The results of this study are in line with research by (Nugraha, et al 2021) who found there are three aspects of the performance of product attributes: customer expectations, company products and competitor products. The performance of customer expectations is the level of customer expectations for a product.…”
Section: Research Findingsupporting
confidence: 90%
“…The results of this study are in line with research by (Nugraha, et al 2021) who found there are three aspects of the performance of product attributes: customer expectations, company products and competitor products. The performance of customer expectations is the level of customer expectations for a product.…”
Section: Research Findingsupporting
confidence: 90%
“…The development of the times and the impact of globalization have made it easy for foreign cultures to enter Indonesia; one example is Korean culture. Globalization's main impact is felt in our shifting identities, growing online cultures, and work models that often clash with traditional values (Nugraha et al, 2021). Korean Wave or Hallyu is a term that is often used to describe the phenomenon of Korean popular culture, better known as K-pop culture (Suryani, 2014).…”
Section: Introductionmentioning
confidence: 99%